2003
DOI: 10.1001/archinte.163.18.2165
|View full text |Cite
|
Sign up to set email alerts
|

Bone Mineral Density Measurement and Treatment for Osteoporosis in Older Individuals With Fractures

Abstract: Evaluation and treatment rates for osteoporosis in older individuals with fractures fall far below national recommendations, especially for men. Intervention strategies should be developed and evaluated to prevent refracture in older individuals with fractures.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
114
1
4

Year Published

2005
2005
2014
2014

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 207 publications
(124 citation statements)
references
References 39 publications
5
114
1
4
Order By: Relevance
“…Despite the prevalence of fracture(s), few had been referred for BMD measurement and only 57 (14%) of 400 subjects with fracture who had responded to the invitation had in fact been treated for osteoporosis. This finding is in accordance with other reports (Freedman et al 2000, Andrade et al 2003, Feldstein et al 2003.…”
Section: Discussionsupporting
confidence: 94%
“…Despite the prevalence of fracture(s), few had been referred for BMD measurement and only 57 (14%) of 400 subjects with fracture who had responded to the invitation had in fact been treated for osteoporosis. This finding is in accordance with other reports (Freedman et al 2000, Andrade et al 2003, Feldstein et al 2003.…”
Section: Discussionsupporting
confidence: 94%
“…The demographic data of this disease have shown that hip fractures throughout globe will rise from 1.66 million in 1990 to 6.26 million by 2050 (Dhanwal et al, 2011). It is characterized by low bone mass and micro architectural deterioration of bone tissue, finally increasing the susceptibility of bone fracture with a low energy trauma (Feldstein et al, 2003). National Institute of Health consensus statement defines OP as ''a skeletal disorder characterized by compromised bone strength predisposing a person to an increased risk of fracture'' (NIH Consensus Development Panel on Osteoporosis Prevention, Diagnosis, and Therapy, 2001).…”
Section: Introductionmentioning
confidence: 99%
“…The guidelines do not tell us how to integrate multiple clinical risk factors or how to integrate clinical risk factors and BMD. The plethora of variable treatment guidelines may sometimes serve to confuse more than enlighten (20) and contribute to their underutilization in clinical practice (21). Population-based strategies identify more patients at high fracture risk for treatment than do case-based strategies, but require more healthcare resources (e.g., BMD testing devices, trained personnel), generate greater costs, and may result in some patients at low risk for fracture being treated.…”
Section: Intervention Thresholdsmentioning
confidence: 99%